2021
DOI: 10.3233/bme-196014
|View full text |Cite
|
Sign up to set email alerts
|

Pericardial fluid and vascular tissue engineering: A preliminary study

Abstract: BACKGROUND: The heart is surrounded by a membrane called pericardium or pericardial cavity. OBJECTIVE: In this study, we investigated the pericardial fluid (PF) for coating polycaprolactone (PCL) scaffolds. PFS, which is a PF component, was used for coating material. In addition to using PFS for surface coating, MED and fetal bovine serum (FBS) were also used for comparison. METHODS: Pericardial fluid cells (PFSc) isolated from PF were cultured on coated PCL scaffolds for 1, 3 and 5 days. Cell viability was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…The harvesting of PF from bovine hearts was described in our previous studies. 42,[46][47][48] Briefly, the thoracic cavity was opened carefully to avoid damaging the pericardium. The PFs were aspirated from the pericardial cavities without removing any organs, by the side of the heart apex with 50-mL sterile syringes, maintained at room temperature, and transported to the laboratory.…”
Section: Obtaining Pf From Bovinementioning
confidence: 99%
See 3 more Smart Citations
“…The harvesting of PF from bovine hearts was described in our previous studies. 42,[46][47][48] Briefly, the thoracic cavity was opened carefully to avoid damaging the pericardium. The PFs were aspirated from the pericardial cavities without removing any organs, by the side of the heart apex with 50-mL sterile syringes, maintained at room temperature, and transported to the laboratory.…”
Section: Obtaining Pf From Bovinementioning
confidence: 99%
“…With SEM images and MTT analysis, it was concluded that cell viability and cell adhesion were better in PCL scaffolds coated with PFS on days 1, 3, and 5. 42 The effect of PFS on cell viability and cell retention is that PF contains complex protein structures such as albumin, globulins, macroglobulins, and fibrinogen. 27,42,43 The PCL scaffold is widely used in biomedical research with its biocompatible, mechanically durable, and biodegradable properties; its hydrophobic features negatively affect cell adhesion.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Biodegradable, low-molecular-weight (10 kDa), and high-molecular-weight (85 kDa) ε-PCLs, approved by the Food and Drug Administration (FDA), have been synthesized from ε-caprolactone monomers under tin octoate catalyst following earlier studies [26,27]. The synthesized ε-PCL scaffolds were prepared by mixing low-molecular-weight (80%) and high-molecular-weight polymers (20%).…”
Section: Preparation Characterization and Sterilization Of ε-Pcl Scaf...mentioning
confidence: 99%